Características de cepillado y lijado de 33 especies de madera - Martínez-Pinillos Cueto, Enrique; Martínez Castillo, José Luis (Instituto de Ecología, A.C., 2016)
The lack of knowledge about wood machining properties may be one of the reasons that potentially commercial wood is not utilized. For this reason it is necessary to perform wood machining tests. This paper presents the results of planing and sanding tests carried out on thirty-three wood species from different regions of Mexico. In a previous study, three types of tests were carried out: boring, mortising and shaping. The ASTM D-1666-64 (American Society for Testing and Materials) Standard methodology was followed. For planing, three different knife angles were used: 20º, 25º and 30º. For sanding tests, three kinds of sandpapers were used: 60, 80 and 100 grade. Results were grouped according to the surface quality obtained. This information could be useful for those involved in manufacturing wood products since it indicates the surface quality for each of the species tested when subjected to the above mentioned machining processes.